2009
DOI: 10.1186/1471-2369-10-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of markers of oxidative stress, inflammation and arterial stiffness between incident hemodialysis and peritoneal dialysis patients – an observational study

Abstract: BackgroundPatients on peritoneal and hemodialysis have accelerated atherosclerosis associated with an increase in cardiovascular morbidity and mortality. The atherosclerosis is associated with increased arterial stiffness, endothelial dysfunction and elevated oxidative stress and inflammation. The aims of this study are to investigate the effects of peritoneal and hemodialysis on arterial stiffness, vascular function, myocardial structure and function, oxidative stress and inflammation in incident patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 29 publications
2
12
0
1
Order By: Relevance
“…Obtain an optimal quality of measured waves is the basic condition for a correct PWV analysis. As already demonstrated by Covic et al 28 in 48 predialysis, 20 dialysis, and 18 transplant patients, and Fassett et al 29 in 144 patients with acute kidney injury, site is indifferent for the results.…”
Section: Resultsmentioning
confidence: 80%
“…Obtain an optimal quality of measured waves is the basic condition for a correct PWV analysis. As already demonstrated by Covic et al 28 in 48 predialysis, 20 dialysis, and 18 transplant patients, and Fassett et al 29 in 144 patients with acute kidney injury, site is indifferent for the results.…”
Section: Resultsmentioning
confidence: 80%
“…Dialysis patients have increased AS compared to the general population and ESRD is considered as a risk factor for AS [23]. It has been suggested that older age, high blood pressure, vascular calcification, fluid overload, inflammation, increased sympathetic activity, activation of the renin-angiotensin system, increased low density lipoprotein (LDL) oxidation, and abnormalities of the nitric oxide system may play a role in arterial wall dysfunction, eventually leading to an increase in arterial stiffness [24][25][26][27]. IR has been shown to be correlated with AS in several populations including type 2 diabetes patients, obese subjects and postmenopausal women [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…While initiation of hemodialysis may partially reduce C-reactive protein (CRP) levels, this was not observed during PD initiation, suggesting different effects of individual dialysis techniques on the inflammatory outcome [4]. Regardless of the differences in techniques, inflammation in PD patients is associated with a poor prognosis, with accelerated atherosclerosis, and an increase in cardiovascular morbidity and mortality [5]. The atherosclerosis is associated with increased arterial stiffness, endothelial dysfunction and elevated oxidative stress and inflammation.…”
Section: Inflammation In Pdmentioning
confidence: 99%